Prevalence and Factors Associated with Post-Cesarean Section Infection in Kigali City Hospitals, Rwanda - Ishimwe, Patrick; Habtu, Michael (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study aimed to assess the prevalence and factors associated with post-cesarean section infections in selected hospitals in Kigali City, Rwanda. Post-cesarean infections significantly contribute to maternal morbidity and healthcare costs, particularly in low-resource settings. Understanding the risk factors is crucial for improving maternal outcomes. A cross-sectional study was conducted among 270 women who underwent cesarean sections, selected through systematic random sampling. Data were gathered using structured questionnaires and medical record reviews. Descriptive statistics summarized socio-demographic and clinical characteristics, while bivariate and multivariable logistic regression analyses identified associated factors. The prevalence of post-cesarean section infections was 13.7% (n = 37). Most participants were aged 25–44 years, married, and had tertiary education. Infections were more common among women who were single, unemployed, had low income, lacked health insurance, or lived over 20 km from the hospital; however, these associations were not statistically significant. Postoperative complications emerged as the only significant predictor of infection (AOR = 3.06, 95% CI: 1.08–8.65, p = 0.034). Other variables such as age, marital status, education, employment, income, type of cesarean section, and use of antibiotic prophylaxis were not significantly associated. The study underscores the need for enhanced postoperative care, with particular attention to preventing and managing surgical complications. Strengthening infection control protocols, ensuring quality wound care, and promoting hygiene practices are essential. Policymakers should expand health insurance coverage and invest in system-level improvements to reduce infection risk and improve maternal health outcomes in Kigali City hospitals.